Pengaruh Fraud Hexagon Theory Terhadap Fraudulent Financial Statement: Studi pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2023 - Risa Putri Wahyu Wulansari; Muhammad Abdul Aris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of fraud hexagon theory on fraudulent financial statements. This study includes quantitative research. The population used is all state-owned companies listed on the Indonesia Stock Exchange for the period 2020-2023 which has a total of 27 companies. The sampling technique used in this study is saturated sampling technique. This study used a type of secondary data. The results can be concluded that stimulus, capability, collusion, rationalization does not affect the fraudulent financial statement, While opportunity and ego have an effect on fraudulent financial statement